INTELLIGENT PEDAGOGIES: AI IN VISUAL ARTS EDUCATION - Kataria, Ansh; Manhas, Rashmi; Ingale, Kiran Ingale; Saxena, Kumud; Pandher, Gurdeep Kaur; Ramakrishnan, Udaya (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Intelligent Pedagogies: AI in Visual Arts Education addresses the disruptive possibilities of artificial intelligence in the design of creative learning systems of the next generation. With the closer interactions between visual arts education and digital technologies, AI-based systems (convolutional neural networks (CNNs) to generative adversarial networks (GANs), transformer-based evaluators, and more) allow more adaptive, responsive, and creativity-amplifying instructional models. This paper explores the learning merit of incorporating smart technology in curriculum development, studio learning, critique, and portfolio building. It also brings out the role of AI in promoting visual literacy, conceptual thinking and reinforcing creative trajectories and paths, with the help of multimodal analysis, automated feedback cycles and content creation in real time. This paper will provide a thorough literature review by comparing conventional art education with AI-enhanced systems, where the focus will be on the introduction of intelligent tutoring systems and adaptive learning environments. The approach consists of selected datasets in the context of art education, the experimental implementation of multimodal AI models, and the development of the teacher-AI-student triadic interaction model. The results of the experiment indicate significant changes in the level of engagement, creativity indicators, iterative refinement behaviors, and the learning process, proving the fact that AI assistance improves not only the technical performance but artistic decision making.